Negative and positive cross-correlations of current noises in quantum Hall edge channels at bulk filling factor ν=1. (28th April 2017) - Ota, T; Hashisaka, M; Muraki, K; Fujisawa, T
Abstract: Cross-correlation noise in electrical currents generated from a series connection of two quantum point contacts (QPCs), the injector and the detector, is described for investigating energy relaxation in quantum Hall edge channels at bulk filling factor ν = 1 . We address the importance of tuning the energy bias across the detector for this purpose. For a long channel with a macroscopic floating ohmic contact that thermalizes the electrons, the cross-correlation turns from negative values to the maximally positive value (identical noise in the two currents) by tuning the effective energy bias to zero. This can be understood by considering competition between the low-frequency charge fluctuation generated at the injector, which contributes positive correlation, and the partition noise at the detector, which gives negative correlation. Strikingly, even for a short channel without intentional thermalization, significantly large positive correlation is observed in contrast to negative values expected for coherent transport between the two QPCs.